Economic impact of tourism in Barangay Maharlika East, Tagaytay City and it's implication to the local residents. - Camatog, Joanne Marie F. (2011)
ABSTRACT Title: “Economic Impacts of Tourism in Barangay Maharlika East, Tagaytay City and its implication to the local residents” Proponents: CAMATOG, JOANNE MARIE F. ARENGA, KRISTOFFER C. CUBILO, ANGELICA O. DONEZA, KATHLEEN B. HERNANDEZ, MARIA ELIZABETH R. MATSUO, YURI M. PLACERO, MA. EDELYN Y. REMETILLA, ARIANNE KAYE B. ROXAS, DIXY KARREN TRACY A. Degree: Bachelor of Science in Tourism Management Adviser: Ernesto Mandigma Jr., MBA, MPA, MAED Purpose of the study The study emphasize on the economic impacts of tourism in Barangay Maharlika East, Tagaytay City and its implication to the local residents. The respondents of this study involved one hundred (100) head of the households of Barangay Maharlika East in Tagaytay City who were selected randomly. A survey was used to collect data on residents’ perception about the Impact of tourism on their livelihood and quality of life. Another limitation is evaluation on the Impact of tourism in the quality of life of the residents which was measured in four (4) dimensional models, namely: material well-being, community well-being, emotional well-being and health and safety well being. The study was conducted during first semester of Academic Year 2011-2012. All information, facts and details are based on the information’s and answer of the residents of Barangay Maharlika East answer on the tool used. Methodology The method that the researchers used is the descriptive method, the most applicable method for the purposed of the study. According to Shuttlewoth, Martyn(2008) Descriptive Research Design is a valid method for researching specific subjects and as a precursor to more quantitative studies. It is a scientific method which involves observing and describing the behavior of a subject without influencing it in any way. The study involved data gathering through a survey utilizing the questionnaire technique and interview. In a survey analyzes a situation in its relative entirely, carefully and comprehensively. In this study the researchers want to determine the Economic Impacts of tourism in Barangay Maharlika East, Tagaytay City and it’s implication to the local residents. The researchers utilized the survey technique by collecting data of the demographic profile of the respondents. Conclusion In the light of the above from the findings the following conclusions are drawn from the study: De La Salle University – Dasmariñas 10 1. The respondents were mostly 40 to 49 years old, Male, Married, with children, household head, high school graduate and occupation are most self employed and the type of occupation are not related in tourism industry. 2. Based on the survey that researchers gathered, the sources of their livelihood shows income increase since tourist began visiting the city. 3. The respondents agreed when it comes to Material Well-Being if the tourism increases their income will also be increase or be more. In the Community Well Being they agreed that Tourism attracts more spending and investment in the community’s economy. For Emotional Well-Being the respondent’s leisure activity is dissipated due to tourism. In terms of Health and Safety Well-Being based on the respondent’s the Barangay is overall clean. 4. There is no significant relationship between socio-demographic profiles of the respondents of Barangay Maharlika east when it comes on the Impact of Livelihood in quality of Life. 5. The researchers output is to Proposed Sustainable Economic Development Program. RECOMMENDATIONS In the light of the findings and conclusions of the study, it is the researchers hope that the following recommendation will be carried out. 1. For the tourism students they may use this study as their reference and have an idea about Economic Impacts of Tourism in Barangay Maharlika East, Tagaytay City and its implication to the local residents. De La Salle University – Dasmariñas 11 2. The more livelihood and quality of life information should be addressed the residents of the heads of the Barangay to improve their knowledge about the livelihood and quality of life, if so they more aware of Impacts of Tourism. Heads of household should participate on livelihood programs of the Barangay to enhance the quality of life. 3. Since economic status of the respondents affects their livelihood and quality of life. The government should impose more policies and programs that will enable them to find more suitable jobs can subsequently improve their socioeconomic status. 4. The tourist should be aware of the policies of the destination. They should be aware how to dispose their waste and they should know how to take care the environment. 5. To researchers themselves should provide copies of their study so that the respondents of the said Barangay know how to sustain their place. 6. To the future researchers must have further study conducted on the same study with Economic Impacts of tourism and more specific question so as to have accurate information.